Multipole effects in atom-surface interactions: a theoretical study with an application to He-α-quartz - Łach, Grzegorz; DeKieviet, Maarten; Jentschura, Ulrich D. (Physical review. A, Atomic, molecular, and optical physics, 2010)
We address some practically important and experimentally relevant questions concerning atom-surface interactions. For example, the quadrupole interaction of an atom with a dielectric macroscopic surface is obtained with full allowance for retardation and in closed form, valid for an arbitrary atom-surface distance. We also explore the relevance of higher-order multipole effects in atom-surface interactions, and we find that details in the dielectric response function of the surface material have to be resolved in order to accurately calculate the atom-surface potential. They lead to important effects at an intermediate range which cannot be explained by either short-range or long-range asymptotics. A numerical example (helium interacting with α-quartz) is included in order to illustrate this aspect.
Gesehen am 09.03.2023